Virtual scarcity: the evolution of imbalance and its impact on society and the environment - Gallaway, Terrel A., author; Kling, Robert, advisor; Bernasek, Alexandra, committee member; Revier, Charles F., committee member; Sparling, Ed, committee member (Colorado State University. Libraries, 2001)
This study examines the historic, cultural, and institutional roots of social-provisioning biases of modem capitalist society that create a profound tendency towards the social creation and perpetuation of scarcity. Though socially unfulfilling and ecologically damaging, the scarcity disposition coordinates society in such a way that ever-increasing production becomes the most believable solution to society's ills. This study explores concepts of scarcity from classical economists to modem writings on thermodynamics and ecological constraints. It shows that modem scarcity has more to do with the lack of balance between social and material progress envisioned by Mill, Godwin, and Condorcet than it does with the constraint on progress envisioned by Malthus and Ricardo. Social articulation and ecotones are used to examine the causes and consequences of this lack of balance. Social articulation, as introduced by this study, is the way individuals evaluate the world and express their desires in a fashion considered appropriate and which coordinates social provisioning. These patterns of evaluation and expression are, to a large degree, social in their origins and consequences. There is a contradiction in our society's prevailing social articulation. Its key elements, like individualism, acquisitiveness, and materialism, make society enormously productive in the material sense while simultaneously cultivating feelings of insufficiency even in the midst of affluence. This research also introduces the concept of ecotones to the study of economics. In ecology, ecotones are the conjuncture of two or more ecological systems. As with ecology, the conjunctions found in economics provide both a unique set of incentives and a locus for a great deal of activity. While biophysical ecotones have shaped economic anthropology and economic geography, more abstract ecotones between systems of value and between other institutions also shape the economy. Specifically, social articulation creates an ecotone between readily articulated commercial values and muted noncommercial values. The asymmetry in articulation favors commodities, allowing the market to encroach upon a greater share of our lives. This intensive and extensive growth in the role of commodities, at the expense of other things of value, at once drives production and perpetuates the construction of scarcity.
Keywords: environmental science; studies; impact analysis; vaccines; happiness; evolution; food; families and family life; ethics; expenditures; traffic congestion; modems; bias; poverty; life expectancy; environmental conditions; society; famine; copyright; households; literacy; affluence